Discovery and functional characterization of a bombesin-type neuropeptide signaling system in an invertebrate - Weiling Huang; Xingxing Zhong; Cleidiane G. Zampronio; Andrew R. Bottrill; Kite G. E. Jones; Ana B. Tinoco; Lijin Guo; Michaela Egertová; Olivier Mirabeau; Maurice R. Elphick (Proceedings of the National Academy of Sciences, 2025)
Neuropeptide signaling systems are key regulators of physiological and behavioral processes in animals. However, the evolutionary history of some neuropeptides originally discovered in vertebrates is unknown. The peptide bombesin (BN) was first isolated from the skin of the toad Bombina bombina and subsequently BN-related neuropeptides have been identified in other chordates, including gastrin-releasing peptide (GRP) and neuromedin B (NMB) in mammals, and a GRP-like peptide in the cephalochordate Branchiostoma japonicum . However, BN-type neuropeptides have hitherto not been identified in any nonchordate animals. Here, we report the discovery and functional characterization of a BN-type neuropeptide signaling system in an echinoderm—the starfish Asterias rubens . BN-type precursor proteins were identified in several echinoderm species based on their amino acid sequences and gene structures, and the mature structure of the A. rubens BN-type neuropeptide ArBN was determined using mass spectrometry. A protein related to vertebrate GRP/NMB-type G protein–coupled receptors was identified experimentally as the receptor for ArBN in A. rubens . Analysis of the distribution of the ArBN precursor in A. rubens using mRNA in situ hybridization and immunohistochemistry revealed a widespread pattern of expression in the central nervous system, digestive system, and locomotory organs. Moreover, effects of ArBN in A. rubens included contraction and retraction of the evertible stomach and inhibition of feeding behavior. Our findings show that the evolutionary history of BN-type neuropeptide signaling can be traced back to the deuterostome common ancestor of echinoderms and chordates. Furthermore, an ancient role of BN-type neuropeptides as regulators of feeding behavior has been revealed.